Modernizing Muscovy : reform and social change in seventeenth-century Russia - Kotilaine, Jarmo; Poe, Marshall (RoutledgeCurzon studies on the history of Russia and Eastern Europe, 2004)
Discusses the nature and extent of 'modernization' in seventeenth century Russia, before Peter the Great's accession, showing that, contrary to the popular view, therewas a great deal of modernization in this period.